2019
DOI: 10.1242/jcs.217521
|View full text |Cite
|
Sign up to set email alerts
|

HsSAS-6-dependent cartwheel assembly ensures stabilization of centriole intermediates

Abstract: At the onset of procentriole formation, a structure called the cartwheel is formed adjacent to the pre-existing centriole. SAS-6 proteins are thought to constitute the hub of the cartwheel structure. However, the exact function of the cartwheel in the process of centriole formation has not been well characterized. In this study, we focused on the functions of human SAS-6 (HsSAS-6, also known as SASS6). By using an in vitro reconstitution system with recombinant HsSAS-6, we first observed its conserved molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Thus, we examined whether the observed structure of NuMA could be attributed to the inhibition of PLK4 or to the low microtubule density induced by the removal of centrosomes. Monopolar‐ and bundle‐like NuMA structures were similarly observed in centrosome‐eliminated cells after Sas6 depletion using the AID system (Appendix Fig S2E; Yoshiba et al , ), suggesting that the aforementioned phenotype was not the result of PLK4 inhibition. We further confirmed that the microtubule density in the acentrosomal spindle was higher than that in the centrosomal spindle (Appendix Fig S2F).…”
Section: Resultsmentioning
confidence: 89%
“…Thus, we examined whether the observed structure of NuMA could be attributed to the inhibition of PLK4 or to the low microtubule density induced by the removal of centrosomes. Monopolar‐ and bundle‐like NuMA structures were similarly observed in centrosome‐eliminated cells after Sas6 depletion using the AID system (Appendix Fig S2E; Yoshiba et al , ), suggesting that the aforementioned phenotype was not the result of PLK4 inhibition. We further confirmed that the microtubule density in the acentrosomal spindle was higher than that in the centrosomal spindle (Appendix Fig S2F).…”
Section: Resultsmentioning
confidence: 89%
“…However, in the absence of ATAD5, ID1 is released from UAF1, thereby free ID1 accumulates at centrosome, leading to centrosome defects. [45]. Recruitment of Sas-6 to the centrioles is promoted by Polo-like kinase 4 (Plk4) and SCL/ TAL1 interrupting locus (STIL) [46].…”
Section: Discussionmentioning
confidence: 99%
“…pool is integrated into cartwheels. Along this line of thought, a recent paper could not detect cenriole assembly defects in a SAS-6 degradation system despite a significant reduction in its levels [14]. [14,26].…”
Section: Model Predictions and Limitationsmentioning
confidence: 99%
“…Along this line of thought, a recent paper could not detect cenriole assembly defects in a SAS-6 degradation system despite a significant reduction in its levels [14]. [14,26]. Second, a specialised atomic-force microscopy protocol has enabled cartwheel ring assembly to be imaged live [27].…”
Section: Model Predictions and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation